Effects of the DRD4 −521 C/T SNP on Local Neural Activity and Functional Connectivity in Children With ADHD - Zhang, Huan; Yang, Binrang; Peng, Gang; Zhang, Linlin; Fang, Diangang (Frontiers in Psychiatry, 2022)
Objective: The present study aimed to investigate the effect of DRD4 −521 C/T SNP on brain function in children with ADHD. Methods Using regional homogeneity, fractional amplitude low-frequency fluctuations and functional connectivity as measurement indexes to compare the differences in resting state brain function between 34 ADHD boys with TT homozygous group and 37 ADHD boys with C-allele carrier group. Results Both regional homogeneity and fractional amplitude low-frequency fluctuations found that the TT homozygous group had lower activation in the right middle occipital gyrus than the C-allele carrier group, and TT homozygous group had decreased functional connectivity in the left superior frontal gyrus and left precuneus. In addition, we found that functional connectivity in the left precuneus was positively correlated with working memory in the TT homozygous group. Conclusions DRD4 −521 C/T SNP has different effects on the brain function of ADHD boys. These findings promote our understanding of the genetic basis of neurobiological abnormalities in ADHD children.